CONFRONTATION OF ALBANIAN LEADERS WITH GLOBAL CRISIS AND THEIR CHARACTERISTICS - Shoraj, Dritan; Llaci, Shyqyri; Zogjani, Adem (European Scientific Journal, ESJ, 2013)
The Albanian leaders were not prepared to face the requirements of a capitalist economy due to the transition of Albania, from a centralized economy to a market economy. Many state enterprises and institutions in Albanian were privatized, and local and global competition required from the organizational leaders to growingly face issues warranted long-term solutions. Organizations and businesses of every kind were facing a challenging environment of where to operate. New emerging requirements made a large number of organizations not flexible to the new financial local situation. Consequently, development appeared as an impossible objective to be achieved. Being unable to avail themselves of scarce opportunities caused difficulties to many local organizations and managers. The managers, owners, employees and consumers were unprepared in response to this situation, and this has brought about dissatisfaction. The theoretical and empirical analysis in this study will elaborate the role of leaders and managers in achieving the objectives of organizational effectiveness, and the steps to overcome financial crisis difficulties in Albania.